Review of the species of Aclees described by Kȏno (Coleoptera: Curculionidae: Molytinae) - Meregalli, Massimo; Boriani, Marco; Bollino, Maurizio; Hsu, Chen-Fu (Zootaxa, 2020)
Lectotypes and paralectotypes of Aclees taiwanensis Kȏno, 1933 and A. hirayamai Kȏno, 1933 are designated and illustrated. The holotype of A. saipanensis Kȏno, 1942 is illustrated.